Coupled analytical and numerical approach to uncovering new regulatory mechanisms of intracellular processes - Śmieja, Jarosław (Zielona Góra: Uniwersytet Zielonogórski)
The paper deals with the analysis of signaling pathways aimed at uncovering new regulatory processes regulating cell responses. First, general issues of comparing simulation and experimental data are discussed, and various aspects of data normalization are covered. Then, a model of a particular signaling pathway, induced by Interferon-?, is briefly introduced. It serves as an example illustrating how mathematical modeling can be used for inferring the structure of a regulatory system governing the dynamics of intracellular processes.
Keywords: signaling pathways; equilibrium points; simulation